2020
DOI: 10.2174/1874210602014010615
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Practice, Motives and Barriers Towards Scientific Research among Dentists and Dental Students in Saudi Arabia

Abstract: Background: Research is crucial for the scientific progress of the health of individuals, communities, and systems. The aim of this study was to assess the knowledge, attitude, motives and barriers among dentists and dental students in the western region of Saudi Arabia. Objective: This study aims to assess the level of knowledge, attitude, motives and barriers toward scientific research among dentists and dental stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…En cambio, los hallazgos están alineados con lo encontrado por Duong & Thi (2022) en Vietnam, quienes valoraron el rol de los docentes para mejorar la actitud hacia la ciencia, por ello, se coincide en que se debería considerar asesores especializados en investigación que apoyen a los estudiantes, tal como lo propone Abdulrahman et al (2020). Esta labor, como lo concluye Castro-Rodríguez (2021), debe contemplar el compromiso de las universidades para impulsar el involucramiento de los estudiantes hacia la ciencia.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…En cambio, los hallazgos están alineados con lo encontrado por Duong & Thi (2022) en Vietnam, quienes valoraron el rol de los docentes para mejorar la actitud hacia la ciencia, por ello, se coincide en que se debería considerar asesores especializados en investigación que apoyen a los estudiantes, tal como lo propone Abdulrahman et al (2020). Esta labor, como lo concluye Castro-Rodríguez (2021), debe contemplar el compromiso de las universidades para impulsar el involucramiento de los estudiantes hacia la ciencia.…”
Section: Discussionunclassified
“…Por ello, la universidad debe promover la investigación para que se genere un mayor interés de los estudiantes universitarios en la ciencia y, para lograrlo, se requiere la asignación de un asesor o supervisor de investigación científica para orientar las actividades de investigación de los estudiantes, como también lo mencionan Abdulrahman et al, (2020) y Pop et al, (2022.…”
Section: Discussionunclassified
“…Other important barriers to research such as lack of acknowledgment, mentorship, opportunities for presentation, and statistical support for research were identified in a considerable proportion in our study and have also been brought to light previously by a Saudi Arabian study [ 21 ]. Lack of both technical and financial support and motivation were also faced by the participants as recognized by another Indian study [ 22 ]. Most of the students believe that there is a lack of awareness of basic research concepts among students.…”
Section: Discussionmentioning
confidence: 99%
“…Research in oral hygiene not only impacts the immediate practice of dentistry but also influences its long-term development and the quality of patient care, thus significantly shaping the dental profession [4] . Efforts to encourage research engagement among dental students have been introduced through various activities.…”
Section: Introductionmentioning
confidence: 99%